NPS: como esse indicador pode impactar o resultado microempresarial - Souza, Emerson de (Universidade Federal de São Carlos, 2022)
Customer success during the purchase process of a product or service has become increasingly important for the financial impact of companies, ensuring that the customer be the focus. Consequently, the entire ecosystem benefits from micro-enterprise success. To map and boost the business, there is a metric called NPS (Net Promoter Score), developed by Reichheld in 2003, whose objective is to measure the level of customer satisfaction with that product or service. In this work, the objective is to Simulate a customer satisfaction analysis for a fictitious company.
NPS: how this indicator can impact the micro-enterprise result
Keywords: Indicador de desempenho; Performance; Serviço ao cliente; Net promoter score; CIENCIAS EXATAS E DA TERRA::FISICA